Islamic Foreign Policy: Principles and Practices - Aswar, Hasbi; Rakhmat, Muhammad Zulfikar (Islamic Research, 2023)
Islam is a comprehensive religion and ideology that encompasses all aspects of human life. However, many Muslims today misunderstand or misinterpret its holistic concept. This issue arises from intellectual limitations within the Muslim community and the pervasive influence of secularism and liberalism in the Islamic world. This article aims to clarify Islam’s perspective on domestic and foreign politics, focusing on its principles, objectives, and practices to provide a more accurate understanding of Islamic foreign policy. Using a qualitative approach, this study collects data from Islamic sources and other relevant literature to explore the foundational concepts of Islamic foreign policy, including both theoretical and practical frameworks. The study argues that Islam forms the basis of Islamic foreign policy, primarily aimed at spreading its message (da'wah). This can be achieved through two main approaches: forceful means (warfare) and peaceful strategies (diplomacy). The paper highlights the importance of consulting expert analyses to optimize foreign policy interests in line with Islamic principles. This research provides foundational insights into Islamic foreign policy and underscores the need for further detailed studies on practical and specific issues in this area. Future research should focus on actionable strategies to implement Islamic foreign policy in a modern global context.